The impact of rural and urban dialect mixing on social identity in Jordan: a study of spontaneous and affected linguistic shifts. - Hazaymeh, Omar Mohammad-Ameen Ahmad (Social Identities, 2025)
This study aimed to analyze the use of rural and urban dialects in Jordan and examine the factors influencing individuals' language choices. The study relied on the descriptive analysis approach using interviews and field observations to examine how individuals use these dialects in different social contexts. The findings revealed that individuals predominantly use the rural dialect in informal settings and rural communities to express cultural identity, whereas they favor the urban dialect in professional and educational contexts. The results also showed that economic and educational factors play a pivotal role in preferring the urban dialect in work environments. The study recommended the need to pay attention to enhancing cultural awareness about the importance of local dialects, and preserving linguistic diversity as part of national identity, in addition to conducting further studies to study the impact of social changes on the use of dialects in urban and rural communities.